Penggunaan Alat Peraga dalam Pengenalan Konsep Matematika pada Anak Usia Dini di TK Al-Falah Kota Cilegon - Dini Riani; Kristiana Maryani (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
This research aims to describe how teachers at Al-Falah Cilegon Kindergarten use teaching materials or props to introduce mathematical concepts and responses or direct impacts experienced by students in the learning process. The subjects in this study were 3 teachers who taught and along with the principal, 5 kindergarten A students and 8 kindergarten students in grade B. Researchers chose qualitative methods because they wanted the results of in-depth research on the phenomenon to be studied. In addition, researchers used this method because the study subjects involved preschoolers who could not be approached with quantitative approaches, such as working on scales and questionnaires, so researchers chose qualitative methods by examining data with in-person interviews, library studies, observations and documentation.